Proyecto arquitectónico de la Escuela Profesional de Medicina Veterinaria - UNSAAC sede Canchis - Cruz Bohorquez, Isai (2019)
Proyecto arquitectónico de la Escuela Profesional de Medicina Veterinaria - UNSAAC sede Canchis